Effect Of Organizational Climate and Organizational Support on Employee Performance at Class 1 Agricultural Quarantine Station Bengkulu City - Amirul Rizky Fajriansyah; Merta Kusuma (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of organizational climate and organizational support on employee performance at the Agricultural Quarantine Station Class 1 Bengkulu City, either partially or simultaneously. There are several factors that will be discussed in this research, including Organizational Climate and Organizational Support. The object of this research is at the Agricultural Quarantine Station Class 1 Bengkulu City, totaling 70 people. In this research, the writer uses the method of collecting data by means of observation, interviews and questionnaires. There are several data analysis techniques used in this study, using instrument tests, namely validity test, reliability test, classical assumption test, coefficient of determination, and also hypothesis testing. From the results of multiple linear regression, the regression equation is obtained as follows: Y = 0.981 + 0.384 (X1) + 0.521 (X2). While the results of the hypothesis testing that have been carried out can be seen that the Organizational Climate variable (X1) obtained tcount of 6.338 (higher than the value of ttable, or ttable> 1.996 (see distribution in table t), and a significance level of 0.000 (significant <0.05) And the Organizational Support variable (X2) obtained tcount of 5.154 (lower than the value of ttable, or ttable < 1.996 (see distribution in table t), and a significance level of 0.319 (significant> 0.05). So it can be concluded that the hypothesis is accepted, meaning that there is Partial or simultaneous influence of Organizational Climate (X1) and Organizational Support (X2) on Employee Performance variable (Y) This can be seen at the significance level of 0.000 < 0.05 at the Agricultural Quarantine Station Class 1 Bengkulu City.